Antibacterial Activity of Trichosanthes cucumerina Linn. Extracts - Arawwawala, L.D.A.M. (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Trichosanthes cucumerina Linn (Family: Cucurbitaceae) is a climber grown in Asian countries including Sri Lanka, India, Malay Penisula and Philippine. The present study was conducted to evaluate whether aerial parts of T. cucumerina can exert antibacterial activity. The antibacterial activity of a hot water extract (HWE) and a cold ethanolic extract (CEE) of T. cucumerina aerial parts was evaluated by (a) viable colony count and (b) disc diffusion techniques against gram (+) and gram (–) bacterial strains such as Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli and Pseudomonas aeroginosa. Results of the present study reveal that T. cucumerina has components that can significantly inhibit the growth of S. aureus, S. pyogenes, E. coli and P. aeroginosa. Of the two extracts tested, CEE was found to exert consistently better antibacterial activity than HWE. In conclusion, T. cucumerina extracts exhibited antibacterial activity against gram (+) ve bacterial strains such as S. aureus, S. pyogenes and gram (-) ve bacterial strains such as E. coli and P. aeroginosa.